2013
DOI: 10.1016/j.jacc.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medications for Secondary Prevention After Coronary Bypass Surgery Compared With Percutaneous Coronary Intervention

Abstract: Patients who received CABG were generally less likely than patients who received PCI to fill prescriptions for secondary preventive medications and to use those medications consistently in the first year after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 26 publications
1
40
4
1
Order By: Relevance
“…[13][14][15][16][17] A large international observational registry (Reduction of Atherothrombosis for Continued Health [REACH]) of 37 154 patients with established atherosclerotic disease has shown that only 46.7% of patients at baseline and 48.2% at 1 year were taking OMT. 29 Although antiplatelet agents and lipid-lowering agents were used in more than two thirds of the SYNTAX patients, use of angiotensin-converting enzyme inhibitor and β-blockers was consistently below 50%, which is similar to the report from CABG patients in the Project of Ex-vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] A large international observational registry (Reduction of Atherothrombosis for Continued Health [REACH]) of 37 154 patients with established atherosclerotic disease has shown that only 46.7% of patients at baseline and 48.2% at 1 year were taking OMT. 29 Although antiplatelet agents and lipid-lowering agents were used in more than two thirds of the SYNTAX patients, use of angiotensin-converting enzyme inhibitor and β-blockers was consistently below 50%, which is similar to the report from CABG patients in the Project of Ex-vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] This underuse of OMT might reflect medication nonadherence or issues with the healthcare system or may be related to a paucity of data, leading to an underestimation of importance of OMT and the misconception that continuing OMT may be of less value once diseased coronary arteries have been mechanically revascularized. 17,18 Recent controversies on the use of β-blockers, generally and in noncardiac surgery, and statins may further reduce prescription or compliance, [19][20][21][22] with potential consequences on long-term clinical outcomes. Therefore, a definitive evaluation of role of OMT in patients with complex CAD undergoing PCI or CABG is warranted.…”
mentioning
confidence: 99%
“…The effect of β-blockers on outcomes has been reported to be influenced by both the initial prescription at the time of hospital discharge, known as physician performance, 2,32,33 and long-term patient adherence after the surgery. 17,29,34 However, little evidence evaluating the combined effect of these 2 individual components is available.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, medication possession ratios for statins, ACEI/ARBs, and β-blockers were lower among post-CABG patients. 9 These observations may reflect both prescribing practices and patient adherence and may be driven by a number of factors, including absolute and relative contraindications or side effects.…”
Section: Improving Use Of Cad Secondary Prevention 1235mentioning
confidence: 99%
“…9 Furthermore, medication possession ratios for statins, ACEI/ARBs, and β-blockers were lower among post-CABG patients. 9 These observations may reflect both prescribing practices and patient adherence and may be driven by a number of factors, including absolute and relative contraindications or side effects. Regardless, in both the SYNTAX and NCDR PINNACLE cohorts, rates of use of all agents were much lower than the high benchmarks for treatment set in the Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) and Bypass Angioplasty Revascularization Investigation-2 Diabetes (BARI-2D) trials, in which there was a focus on use of optimal medical therapy.…”
Section: Improving Use Of Cad Secondary Prevention 1235mentioning
confidence: 99%